The Effect of Zakat, Foreign Debt and Inflation Toward the Economic Growth of Indonesia Through Consumption in 2010-2019 - Nabila, Rifda; Anwar, Malik (Journal of Economics and Regional Science, 2021)
This study aims to examine the effect of zakat, foreign debt, inflation on economic growth with consumption as an intervening variable. This research uses quantitative methods with time series data. The sample used is as much as 40 for each variable from 2010-2019. This research method uses multiple linear regression analysis. The results showed that zakat has a significant positive effect on consumption, foreign debt and inflation have a positive and insignificant effect on consumption, consumption has a significant positive effect on economic growth, zakat has a significant positive effect on economic growth, foreign debt has a negative and insignificant effect on economic growth. Inflation has a positive and insignificant effect on economic growth. Zakat has a significant positive effect on economic growth through consumption. External debt and domestic inflation have an insignificant positive effect on economic growth through consumption.